New phoswich detector based on LFS and p-terphenyl scintillators coupled to micro pixel avalanche photodiode - Ahmadov, F.; Abdullayev, F.; Ahmadov, G.; Sadigov, A.; Sadygov, Z.; Madatov, R.; Suleymanov, S.; Akberov, R.; Heydarov, N.; Nazarov, M. (Functional Materials, 2017)
This paper presents the results of phoswich detector which developed on the basis of micro pixel avalanche photodiode and LFS+p-terphenyl scintillators. The beta particles and gamma rays detection performance of the phoswich detector (LFS+p-terphenyl) was investigated. The energy resolution of monochromatic electron was 23 % (625 keV). The detected count ratio of beta particle and gamma ray was about 37 %. It was obtained that this type of phoswich detector discriminates between gamma rays and beta particles due to the differences in the light decay time of scintillators.